STUDI TENTANG PERUBAHAN TRADISI BELE KAMPUNG DI DESA BOKOR KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Isnani Reffila Dewi; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by a change of Bele Kampung tradition in village Bokor Kecamatan Rangsang Barat Kabupaten Kepulauan Meranti. The formulations of the problem are (1) What aspects have changed Bele Kampung Tradition in the village of Bokor in the West Rangsang Sub-District of Meranti Islands Regency (2) What factors influence the change Bele Kampung tradition in the village of Bokor in the Rangsang Barat Sub-District in the Meranti Islands Regency. Research Objectives (1) To find out what aspects have changed Bele Kampung tradition in the village of Bokor in the West Rangsang Sub-District of the Meranti Islands Regency (2) To find out what factors influence the change Bele Kampung tradition in the village of Bokor in the Rangsang Barat Sub-District in the Meranti Islands Regency. This research is descriptive qualitative. Data collection techniques in this study are, observation, interview, and, documentation. There were 10 informants in this study, the determination of the informants was done by using purposive sampling. The results of this study indicate that there are aspects that have changed in the Bele Kampung tradition. In this study the factors that influence change are the dominant discovery (new discovery) besides that there is also the invention factor (application of new discoveries) but not so dominant.Key Words: Change, Bele Kampung Tradition